Impact of School Massification on the Professional Commitment of Teachers of Public Primary Schools in Kara, Togo - Souglibé NAKPAKPERE; Boussanlègue TCHABLE (Unib Press, 2024)
In its efforts to provide a constant response to the various international education meetings and the requirements of Technical and Financial partners, Togo has adopted new educational policies. Preschool and primary education have now been free since 2008. This free education leads to school massification which influences the professional commitment of teachers. This article starts from the postulate according to which school massification negatively influences the professional commitment of teachers. The aim is therefore to analyze the influence of school massification on the social commitment of teachers in public primary schools in the town of Kara. To do this, a survey was carried out among 129 teachers chosen at random from 11 schools in the city. The research combines quantitative and qualitative methods. The results show that the sample is predominantly male (59%), the average age is 35 years old. The population surveyed (n=129) is mainly a BAC II graduate (n=61) and young (n=73). Teachers believe that free primary school is a source of their unease. Their professional disengagement, which is a consequence of school massification, emanates from this new policy. On the one hand, it creates insufficient infrastructure and a lack of teachers and on the other hand, it has a negative impact on the quality of academic performance.